Discrimination Voltage and Overdrive Bias Dependent Performance Evaluation of Passively Quenched SiC Single-Photon-Counting Avalanche Photodiodes - 刘飞 杨森 周东 陆海 张荣 郑有炓 (Chinese physics letters, 2015)
In many critical civil and emerging military applications, low-level UV detection, sometimes at single photon level, is highly desired. In this work, a mesa-type 4H-SiC UV avalanche photodiode （APD） is designed and fabricated, which exhibits low leakage current and high avalanche gain. When studied by using a passive quenching circuit, the APD exhibits self-quenching characteristics due to its high differential resistance in the avalanche region. The single photon detection efficiency and dark count rate of the APD are evaluated as functions of discrimination voltage and over-drive voltage. The optimized operation conditions of the single photon counting APD are discussed.